First record of the genus Yezoceryx Uchida (Ichneumonidae: Acaenitinae) from Vietnam, with descriptions of nine new species - Pham, Nhi Thi; Broad, Gavin R.; Matsumoto, Rikio; Achterberg, Cornelis Van (Zootaxa, 2017)
On the basis of recent ichneumonid collections from the Institute of Ecology and Biological Resources, Hanoi, Vietnam, the Netherlands Centre for Biodiversity Naturalis, Leiden, Netherlands, and the Osaka Museum of Natural History, Osaka, Japan, the genus Yezoceryx (Ichneumonidae: Acaenitinae) is reported for the first time from Vietnam with descriptions of nine new species, viz. Yezoceryx bicarinatus sp. nov., Y. brevius sp. nov., Y. coronatus sp. nov., Y. pacoensis sp. nov., Y. phui sp. nov., Y. rufus sp. nov., Y. shengi sp. nov., Y. tamdaoensis sp. nov. and Y. thaii sp. nov. In addition, nine further species are recorded for the first time from the country. A key to a total of 18 Yezoceryx species from Vietnam is included. Acaenitus xanthorius Morley, 1913 is a junior synonym of Yezoceryx luteus (Cameron, 1899), syn. nov. The subdivision of Yezoceryx into subgenera is untenable and Yezoceryx (Brevitergus) Wang and Yezoceryx (Longitergus) Wang are both new synonyms of Yezoceryx.